Doping material and organic electroluminescent device and organic electroluminescent device comprising same
By designing new organic electroluminescent materials, using the regulation of heterocyclic ligands and substituents, the problems of reduced efficiency and high driving voltage of phosphorescent OLED devices are solved, and high efficiency, long life and low voltage organic electroluminescent devices are achieved .
Patent Information
- Application Number
- CN202411095023.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-09
- Publication Date
- 2024-12-13
AI Technical Summary
The efficiency of existing phosphorescence OLED devices is rapidly reduced under high brightness conditions and have a high driving voltage, making it difficult to achieve the comprehensive characteristics of high efficiency, long life and low voltage.
Using specific heterocyclic ligands and substituents for regulation, a new organic electroluminescent material is designed to be used for the luminescent layer of organic electroluminescent devices. By mixing with other substances, it optimizes the structure and performance of the device. .
Improves the maximum external quantum efficiency of organic electroluminescent devices, extends the phosphorescence life, and reduces the driving voltage.
Smart Images

Figure CN119119126A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic photoelectric materials, and relates to a novel organic electroluminescent material, a preparation method thereof, and an application thereof in preparing an organic electroluminescent device. Background Art
[0002] Organic electronic devices include but are not limited to the following categories: organic light emitting diodes (OLEDs), organic field effect transistors (O-FETs), organic light emitting transistors (OLETs), organic photovoltaic devices (OPVs), dye-sensitized solar cells (DSSCs), organic optical detectors, organic photoreceptors, organic field effect devices (OFQDs), light emitting electrochemical cells (LECs), organic laser diodes, and organic plasmonic light emitting devices.
[0003] In 1987, Tang and Van Slyke of Eastman Kodak reported a double-layer organic electroluminescent device, which included an arylamine hole transport layer and a tri-8-hydroxyquinoline-aluminum layer as an electron transport layer and a light-emitting layer (Applied Physics Letters, 1987, 51 (12): 913-915). Once a bias voltage is applied to the device, green light is emitted from the device. This invention laid the foundation for the development of modern organic light-emitting diodes (OLEDs). The most advanced OLEDs can include multiple layers, such as charge injection and transport layers, charge and exciton blocking layers, and one or more light-emitting layers between the cathode and the anode. Since OLED is a self-luminous solid-state device, it offers great potential for display and lighting applications. In addition, the inherent properties of organic materials, such as their flexibility, can make them very suitable for special applications, such as on flexible substrates.
[0004] The emission color of OLED can be achieved by designing the structure of the luminescent material. OLED can include one luminescent layer or multiple luminescent layers to achieve the desired spectrum. Commercial full-color OLED displays usually adopt a hybrid strategy, using blue fluorescence and phosphorescent yellow, or red and green. At present, the efficiency of phosphorescent OLEDs decreases rapidly at high brightness, which is still a problem.
[0005] Therefore, how to develop a high-performance phosphorescent material that enables an organic electroluminescent device to have comprehensive characteristics such as high efficiency, long life and low voltage is a technical problem that people in this field need to solve urgently. Summary of the invention
[0006] In view of this, the present invention provides an organic electroluminescent material and a preparation method thereof and an application in an organic electroluminescent device. The organic electroluminescent material provided by the present invention is used as a material in the light-emitting layer of an organic electroluminescent device, so that the driving voltage of the device can be reduced, the maximum external quantum efficiency of the device can be increased, and the phosphorescence life of the device can be prolonged.
[0007] In order to achieve the above objectives, a first object of the present invention is to provide an organic electroluminescent material.
[0008] The following technical solutions are adopted:
[0009] An organic electroluminescent material having a structure shown in general formula I:
[0010]
[0011] wherein m is selected from 0 or 1, further m is selected from 1, and X is selected from O or S;
[0012] R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 , R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 17 , R 18 , R 19 , R 20 , R 21 and R 22 may be independently selected from hydrogen, deuterium, halogen, cyano, isocyano, substituted or unsubstituted alkyl having 1 to 20 carbon atoms, substituted or unsubstituted cycloalkyl having 3 to 20 carbon atoms, substituted or unsubstituted heterocyclic group having 3 to 20 carbon atoms, substituted or unsubstituted aralkyl having 7 to 30 carbon atoms, substituted or unsubstituted alkoxy having 1 to 20 carbon atoms, substituted or unsubstituted aryloxy having 6 to 30 carbon atoms, substituted or unsubstituted aryl having 6 to 30 carbon atoms, substituted or unsubstituted heteroaryl having 3 to 30 carbon atoms, -SiRR'R'', -GeRR'R'', and combinations thereof;
[0013] Wherein R, R', R'' are selected from substituted or unsubstituted alkyl groups having 1 to 20 carbon atoms, and substituted or unsubstituted cycloalkyl groups having 3 to 20 carbon atoms.
[0014] Furthermore, the alkyl group and the aryl group may be partially or fully deuterated.
[0015] Furthermore, LA ligand Select from the following structures:
[0016]
[0017]
[0018]
[0019] Furthermore, LB ligand Select any one of the following structures:
[0020]
[0021]
[0022]
[0023]
[0024]
[0025]
[0026]
[0027]
[0028]
[0029] Furthermore, the formula I is selected from one of the following structural formulas I-1, I-2, I-3, I-4, and I-5:
[0030]
[0031]
[0032] Among them, R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 , R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 17 , R 18 , R 19 , R 20 , R 21 and R 22 As defined above.
[0033] In the above scheme, the organic electroluminescent material is selected from any one of the following structures, but is not limited thereto:
[0034]
[0035]
[0036]
[0037]
[0038]
[0039]
[0040]
[0041]
[0042]
[0043]
[0044]
[0045]
[0046]
[0047]
[0048]
[0049]
[0050]
[0051]
[0052]
[0053]
[0054]
[0055]
[0056]
[0057]
[0058]
[0059]
[0060]
[0061]
[0062]
[0063]
[0064]
[0065]
[0066]
[0067]
[0068]
[0069]
[0070]
[0071]
[0072]
[0073]
[0074]
[0075]
[0076]
[0077]
[0078]
[0079]
[0080]
[0081]
[0082]
[0083]
[0084] Only some specific structural forms are listed above, but this series of organic electroluminescent materials is not limited to the above molecular structures. Other specific molecular structures can be obtained by simple changes of some simple groups and their substituted groups and substitution positions, which will not be described one by one here.
[0085] The second object of the present invention is to provide application of the above organic electroluminescent material in an organic electroluminescent device.
[0086] An electroluminescent device, comprising the organic electroluminescent material. The organic electroluminescent device comprises: an anode, a cathode and an organic layer disposed between the anode and the cathode, wherein the organic layer comprises the organic electroluminescent material of the present invention; the organic electroluminescent material is in a single form or mixed with other substances and exists in the organic layer.
[0087] The organic layer at least includes one or more of a hole injection layer, a hole transport layer, a layer having both hole injection and hole transport skills, an electron blocking layer, a light-emitting layer, a hole blocking layer, an electron transport layer, an electron injection layer and a layer having both electron transport and electron injection skills.
[0088] The organic electroluminescent device comprises at least one functional layer, namely the organic electroluminescent material of the present invention.
[0089] The organic electroluminescent device comprises a light-emitting layer, and the light-emitting layer contains the organic electroluminescent material of the present invention.
[0090] The light-emitting layer of the organic electroluminescent device comprises a main material and a doping material, wherein the doping material is the organic electroluminescent material of the present invention, and the mixing ratio of the main material to the doping material is 90:10 to 99.5:0.5.
[0091] The device of the present invention can be used in organic light-emitting devices, organic solar cells, electronic paper, organic photoreceptors or organic thin film transistors.
[0092] Compared with the prior art, the present invention has the following beneficial effects:
[0093] The present invention provides a doping material, which can improve the maximum external quantum efficiency of an organic electroluminescent device, prolong the life span and reduce the driving voltage by selecting a doping material coordinated with a specific heterocyclic ligand and adjusting the position of a substituent or the activity of a substituent so that the obtained organic electroluminescent material can be used in an organic electroluminescent device. BRIEF DESCRIPTION OF THE DRAWINGS
[0094] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0095] Figure 1 It is the hydrogen nuclear magnetic resonance spectrum of compound G-2 of the present invention. DETAILED DESCRIPTION
[0096] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0097] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.
[0098] Preparation of Example 1G-2
[0099] The specific process is as follows:
[0100]
[0101] Step 1: First, 30 L of 1,4-dioxane, 3-chlorophenol (8.7 mol), biboric acid pinacol ester (10.44 mol), methyl acetate (21.75 mol) were charged into the system under nitrogen atmosphere, and nitrogen was replaced twice. Under nitrogen protection, tris(dibenzylideneacetone)dipalladium (0.087 mol) and 2-dicyclohexylphosphine-2',4',6'-triisopropylbiphenyl (0.696 mol) were added into the system, and nitrogen was replaced twice. The reaction was carried out at 100°C for 12 hours. The mixture was cooled to room temperature, filtered, passed through a silica gel funnel, the filtrate was concentrated, and column chromatography was performed, using petroleum ether and dichloromethane as developing agents to obtain intermediate S1 (1835.87 g), with a yield of 72%.
[0102]
[0103] Step 2: First, DMSO (50 ml), potassium phosphate trihydrate (53.08 g, 250 mmol), pyridine-2-carboxylic acid (1.53 g, 12.44 mmol) and Cu I (1.19 g, 6.22 mmol) were charged under a nitrogen atmosphere. Then, (33.02 g, 150 mmol) and 2-bromo-1-chlorobenzene (23.93 g, 125 mmol) were gradually added in sequence, and the reaction mixture was heated at 85 ° C for 16 h. After cooling, the reaction mixture was extracted with an ammonia solution and methyl tert-butyl ether. The organic phase was washed five times with water, then washed twice with a saturated NaCl solution, and finally, the combined organic phase was dried over anhydrous Na2SO4 and concentrated. Fractionation was performed. Intermediate S2 (25.54 g) was obtained with a yield of 51.6%;
[0104] HPLC: >99%.
[0105]
[0106] Step 3: Under a nitrogen atmosphere, the reaction system of S2 (122.6 mmol) in THF (2000 ml) was cooled to -75°C. Subsequently, n-butyl lithium (2.5 mol / l hexane solution, 25.52 mmol) was added dropwise in a manner that the internal temperature did not exceed -65°C. Stirring was continued at -75°C for 2 h, then gradually warmed to 10°C within 1 h, and stirred at 10°C for 1 h. Finally, it was cooled to 0°C and the reaction system was carefully quenched with saturated Na2SO3 solution (500 ml). Toluene and water were added to the system to extract the mixture, and the organic phase was first washed three times with water, then washed once with a saturated NaCl solution, and finally dried with Na2SO4. Concentrated. Intermediate S3 (16.97 g) was obtained with a yield of 42.17%;
[0107] HPLC: >99.2%.
[0108]
[0109] Step 4: Prepare S4 using the method for preparing S2 to obtain intermediate S4 (20.42 g).
[0110] Yield: 41.25%;
[0111] HPLC: >99.2%.
[0112]
[0113] Step 5: Under nitrogen atmosphere, S4 (23.90 g, 100 mmol) was added to a system with THF (150 ml). When the temperature dropped to -75 °C, n-butyl lithium (2.5 mol / l hexane solution, 80 ml, 200 mmol) was gradually added dropwise to the system, and the internal temperature was controlled not to exceed -65 °C. After the addition was completed, stirring was continued at -75 °C for 4 h, and then bromine (5.6 ml, 109.3 mmol) was added dropwise in a manner of controlling the internal temperature not to exceed -65 °C. After the addition was completed, the mixture was continued to be stirred at -75 °C for 1 h, and then gradually heated to 10 °C within 1 h, and stirred at 10 °C for 1 h. It was then cooled to 0 °C and quenched with a saturated Na2SO3 solution (50 ml). Toluene and water were added to the system to extract the mixture, and the organic phase was first washed three times with water, then washed once with a saturated NaCl solution, and finally dried with Na2SO4. Concentrated. Intermediate S5 (14.42 g) was obtained, yield: 51.25%;
[0114] Purity:>99%;
[0115] Mass spectrometry test value: 279.93.
[0116]
[0117] Step 6: First weigh the intermediate S5 (182.18 mmol), the intermediate S3 (178.61 mmol), anhydrous potassium carbonate (535.83 mmol), toluene (1000 ml), ethanol (500 ml), and water (1000 ml), add them into the reactor, replace the nitrogen, add (tetrakistriphenylphosphine) palladium (1.786 mmol) into the reaction system under nitrogen protection, react at 80 ° C for 10 hours, then cool to room temperature, stand and separate, combine the organic phases, spin dry, column chromatography, develop petroleum ether and dichloromethane, and obtain intermediate S6 (35.58 g), yield: 49.56%.
[0118] HPLC: ≥99.7%;
[0119] Mass spectrometry test value 402.02.
[0120]
[0121] Step 7: Under nitrogen atmosphere, add intermediate S6 (100 mmol) and anhydrous K2CO3 (300 mmol), dimethylacetamide (DMAc, 450 ml) to the reactor in sequence, stir the mixture for 30 min, add Pd(OAc)2 (1.99 mmol) and 1,3-di(2,6-diisopropylphenyl)-3H-imidazole-1-cation chloride (3.98 mmol) to the system, replace nitrogen twice, and react at 150°C for 16 h. After the reaction is completed, cool to room temperature, pour the mixture into ethanol / water (1:1, 600 ml) and stir for 30 min. Filter with suction, wash the solid with water five times, wash with ethanol three times, recrystallize with 2-propanol, and filter to obtain intermediate S7 (14.06 g), yield: 38.42%;
[0122] HPLC: greater than 99%.
[0123] Mass spectrometry test value: 366.04.
[0124]
[0125] Step 8: First weigh the intermediate S7 (136.59 mmol), 2-pyridineboric acid (163.91 mmol), anhydrous potassium carbonate (409.77 mmol), toluene (1000 ml), ethanol (500 ml), and water (1000 ml), replace the nitrogen, add (tetrakistriphenylphosphine) palladium (1.37 mmol) to the reaction system under nitrogen protection, react at 100 ° C for 12 hours, then cool to room temperature, stand and separate, combine the organic phases, spin dry, column chromatography, develop petroleum ether and dichloromethane, and obtain intermediate S8 (44.68 g), yield: 79.97%.
[0126] HPLC: ≥99.8%;
[0127] Mass spectrometry test value: 409.11.
[0128]
[0129] Step 9: Under nitrogen protection, weigh formula A-2 (59.09 mmol), I rC13·3H2O (23.63 mmol) into the reaction system, add a mixed solution of 150 ml ethylene glycol ethyl ether and 50 ml pure water, reflux for 48 hours under nitrogen protection, then cool to room temperature, precipitate, filter the precipitate, rinse and dry with water, anhydrous ethanol, and petroleum ether in turn. Obtain bridged ligand B-2 (12.52 g), yield: 94.02%.
[0130] Step 10: Weigh the bridging ligand B-2 (11.09 mmol), add silver trifluoromethanesulfonate (24.39 mmol), then add 200 ml of dichloromethane to the system, add 60 ml of methanol, react at room temperature for 48 hours under nitrogen protection, pass through a silica gel funnel, and spin dry to obtain intermediate C-2 (15.6 g), yield: 95.12%.
[0131] Step 11: Weigh the intermediate C-2 (21.08 mmol), add the ligand S8 (52.7 mmol), and then add 312 ml of anhydrous ethanol to the system. Under nitrogen protection, reflux for 48 hours, filter, wash with alcohol, and dry. Use a mixture of petroleum ether and dichloromethane as a developing solvent, column chromatography, concentrate the filtrate, and solid precipitate to obtain an organic electroluminescent material G-2 (7.4 g), with a yield of 38.62%.
[0132] HPLC:≥99.3%.
[0133] Mass spectrometry test value: 937.25.
[0134] Theoretical values of elemental analysis: C, 67.93%; H, 3.66%; N, 4.48%; O, 3.41%; tested values: C, 67.97%; H, 3.68%; N, 4.45%; O, 3.42%.
[0135] Preparation of Example 2G-5
[0136] The specific process is as follows:
[0137] Step 1: Prepare intermediate S8 using the same method as in Example 1 to obtain intermediate S8 (44.73 g) with a yield of 80.04%.
[0138] HPLC: ≥99.8%;
[0139] Mass spectrometry test value: 409.16.
[0140]
[0141] Step 2: Under nitrogen protection, weigh formula A-5 (81.85 mmol), I rC13·3H2O (37.2 mmol) into the reaction system, add 300 ml of ethylene glycol ethyl ether and 100 ml of pure water, reflux for 48 hours under nitrogen protection, then cool to room temperature, precipitate, filter the precipitate, rinse and dry with water, anhydrous ethanol, and petroleum ether in turn. Get bridged ligand B-5 (19.4 g), yield: 88.1%).
[0142] Step 3: Weigh the bridging ligand B-5 (16.38 mmol), add silver trifluoromethanesulfonate (36.03 mmol), then add 380 ml of dichloromethane and 126 ml of methanol to the system, react at room temperature for 48 hours under nitrogen protection, pass through a silica gel funnel, and spin dry to obtain intermediate C-5 (22.4 g), yield: 89%.
[0143] Step 4: Weigh the intermediate C-5 (19.52 mmol), add the ligand S8 (48.8 mmol), and then add 300 ml of anhydrous ethanol to the system. Under nitrogen protection, reflux for 72 hours, filter, wash with alcohol, and dry. Use petroleum ether and dichloromethane as a developing solvent, column chromatography, concentrate the filtrate, and solid precipitate to obtain the organic electroluminescent material G-5 (5.08 g, yield 26.96%).
[0144] HPLC: ≥99.3%.
[0145] Mass spectrometry test value: 965.26.
[0146] Theoretical values of elemental analysis: C, 68.45%; H, 3.97%; N, 4.35%; O, 3.32%; tested values: C, 68.55%; H, 4.02%; N, 4.33%; O, 3.28%.
[0147] 1 H NMR(400MHz,Ch loroform-d)δ8.71(dd,1H),8.47(d,2H),8.31(dd,1H),8.05(dd,2H),7.92–7.86(m, 3H),7.82–7.61(m,8H),7.44(ddd,2H),7.33–7.21(m,7H),2.42(s,6H),2.25(d,6H).
[0148] Preparation of Example 3G-22
[0149] The specific process is as follows:
[0150] Step 1: Prepare intermediate S8 using the same method as in Example 1 to obtain intermediate S8 (45.21 g) with a yield of 80.9%.
[0151] HPLC: ≥99.8%;
[0152] Mass spectrometry test value: 409.08.
[0153]
[0154] Step 2: Under nitrogen protection, weigh formula A-22 (81.85 mmol), I rC13·3H2O (32.74 mmol) into the reaction system, add 300 ml of ethylene glycol ethyl ether and 100 ml of pure water, reflux for 48 hours under nitrogen protection, then cool to room temperature, precipitate, filter the precipitate, rinse with water, anhydrous ethanol, and petroleum ether, and dry in turn. The bridged ligand B-22 (32.72 g) is obtained, with a yield of 67.52%.
[0155] Step 3: Weigh the bridging ligand B-22 (8.44 mmol), add silver trifluoromethanesulfonate (18.56 mmol), then add 200 ml of dichloromethane and 50 ml of methanol to the system, react at room temperature for 48 hours under nitrogen protection, pass through a funnel, and spin dry to obtain intermediate C-22 (12.85 g), yield: 99.15%.
[0156] Step 4: Weigh the intermediate C-22 (16.72 mmol), add the ligand S8 (41.8 mmol), and then add 240 ml of anhydrous ethanol to the system. Under nitrogen protection, reflux for 48 hours, filter, wash with alcohol, and dry. Use petroleum ether and dichloromethane as a developing solvent, column chromatography, concentrate the filtrate, and solid precipitate to obtain the organic electroluminescent material G-22 (5.68 g, yield 35.21%).
[0157] HPLC:≥99.3%.
[0158] Mass spectrometry test value: 965.26.
[0159] Theoretical values of elemental analysis: C, 68.45%; H, 3.97%; N, 4.35%; O, 3.32%; tested values: C, 68.52%; H, 4.01%; N, 4.31%; O, 3.29%.
[0160] 1 H NMR(400MHz,Ch loroform-d)δ8.71(dd,1H),8.31(dd,1H),8.08–8.01(m,4H),7.92–7.86(m,3H),7.79–7.72(m,1H),7.68 (d,1H),7.49–7.43(m,2H),7.43–7.38(m,4H),7.36–7.19(m,7H),6.99(dd,2H),2.56(s,6H),2.40(s,6H).
[0161] Example 4 Preparation of G-374
[0162] The specific process is as follows:
[0163] Step 1: Prepare intermediate S7 using the same method as in Example 1 to obtain intermediate S7 (45.33 g) with a yield of 81.12%.
[0164] HPLC: ≥99.8%;
[0165] Mass spectrometry test value: 409.13.
[0166]
[0167] Step 2: first weigh the intermediate S7 (136.59 mmol), 4-methylpyridine-2-boric acid (163.91 mmol), anhydrous potassium carbonate (409.77 mmol), toluene (1000 ml), ethanol (500 ml), and water (1000 ml), replace the nitrogen, add (tetrakistriphenylphosphine) palladium (1.3659 mmol) to the reaction system under nitrogen protection, react at 100°C for 12 hours, then cool to room temperature, stand and separate, combine the organic phases, spin dry, column chromatography, and use petroleum ether and dichloromethane as developing agents to obtain intermediate S9 (44.78 g), with a yield of 77.48%.
[0168] HPLC: ≥99.8%;
[0169] Mass spectrometry test value: 423.13.
[0170]
[0171] Step 3: Under nitrogen protection, weigh formula A-374 (76.03 mmol), I rC13·3H2O (34.56 mmol) and put them into the reaction system, add a mixed solution of 300 ml of ethylene glycol ethyl ether and 100 ml of pure water, reflux for 48 hours under nitrogen protection, then cool to room temperature, precipitate is precipitated, filter the precipitate, rinse and dry with water, anhydrous ethanol, and petroleum ether in turn. The bridged ligand B-374 (18.7 g) is obtained, with a yield of 87.26%).
[0172] Step 4: Weigh the bridging ligand B-374 (15.07 mmol), add silver trifluoromethanesulfonate (33.15 mmol), then add 360 ml of dichloromethane and 120 ml of methanol to the system, react at room temperature for 48 hours under nitrogen protection, pass through a funnel, and spin dry to obtain intermediate C-374 (21.8), yield: 90.9%.
[0173] Step 5: Weigh the intermediate C-374 (18.14 mmol), add the ligand S9 (47.1 mmol), and then add 220 ml of anhydrous ethanol to the system. Under nitrogen protection, reflux for 48 hours, filter, wash with alcohol, and dry. Use a mixture of petroleum ether and dichloromethane as a developing solvent, column chromatography, concentrate the filtrate, and solid precipitate to obtain the organic electroluminescent material G-374 (5.26 g, yield 28.8%).
[0174] HPLC:≥99.3%.
[0175] Mass spectrometry test value 1007.31.
[0176] Theoretical values of elemental analysis: C, 69.16; H, 4.40; N, 4.17; O, 3.18; tested values: C, 69.16; H, 4.40; N, 4.17; O, 3.18.
[0177] 1 H NMR(400MHz,Ch loroform-d)δ8.70(d,1H),8.43(dd,2H),8.31(dd,1H),8.19(d,1H),8.09(d,1H),7.95–7.88(m,2H),7.68–7.62(m,2H),7.61(d,1H) ,7.57(d,2H),7.49–7.39(m,3H),7.30(ddd,2H),7.17–7.11(m,1H),7.08(d,2H),6.91–6.87(m,2H),2.44–2.36(m,15H),2.25(d,6H).
[0178] The synthesis methods of other organic electroluminescent materials G-3, G-11, G-18, G-24, G-63, G-209, G-223, G-281, G-308, G-341, G-371, G-485, G-591, G-643 and G-725 are the same as those in the above embodiments, and are not described in detail here. The molecular formulas, mass spectrometry test values and purities of other synthesized organic electroluminescent materials are shown in Table 1 below:
[0179] Table 1 Molecular formula, mass spectrum and purity of organic electroluminescent materials
[0180] Compound Molecular formula Mass spectrometry test value purity G-3 <h2 style=";text-align:left;direction:ltr"><![CDATA[C <h2 style=";text-align:left;direction:ltr"> 57 <h2 style=";text-align:left;direction:ltr"> H<h2 style=";text-align:left;direction:ltr"> 46 <h2 style=";text-align:left;direction:ltr"> Ge2IrN3O2<h2 style=";text-align:left;direction:ltr"> 1145.16 ≥99.3 G-11 <h2 style=";text-align:left;direction:ltr"><![CDATA[C <h2 style=";text-align:left;direction:ltr"> 55 <h2 style=";text-align:left;direction:ltr"> H<h2 style=";text-align:left;direction:ltr"> 26 <h2 style=";text-align:left;direction:ltr"> D<h2 style=";text-align:left;direction:ltr"> 12 <h2 style=";text-align:left;direction:ltr"> IrN3O2<h2 style=";text-align:left;direction:ltr"> 977.33 ≥99.5 G-18 <h2 style=";text-align:left;direction:ltr"><![CDATA[C <h2 style=";text-align:left;direction:ltr"> 79 <h2 style=";text-align:left;direction:ltr"> H<h2 style=";text-align:left;direction:ltr"> 67 <h2 style=";text-align:left;direction:ltr"> D<h2 style=";text-align:left;direction:ltr"> 19 <h2 style=";text-align:left;direction:ltr"> IrN3O2<h2 style=";text-align:left;direction:ltr"> 1320.75 ≥99.2 G-24 <h2 style=";text-align:left;direction:ltr"><![CDATA[C <h2 style=";text-align:left;direction:ltr"> 55 <h2 style=";text-align:left;direction:ltr"> H<h2 style=";text-align:left;direction:ltr"> 26 <h2 style=";text-align:left;direction:ltr"> D<h2 style=";text-align:left;direction:ltr"> 12 <h2 style=";text-align:left;direction:ltr"> IrN3O2<h2 style=";text-align:left;direction:ltr"> 977.33 ≥99.6 G-63 <h2 style=";text-align:left;direction:ltr"><![CDATA[C <h2 style=";text-align:left;direction:ltr"> 57 <h2 style=";text-align:left;direction:ltr"> H<h2 style=";text-align:left;direction:ltr"> 26 <h2 style=";text-align:left;direction:ltr"> D<h2 style=";text-align:left;direction:ltr"> 16 <h2 style=";text-align:left;direction:ltr"> IrN3O2<h2 style=";text-align:left;direction:ltr"> 1009.39 ≥99.3 G-209 <h2 style=";text-align:left;direction:ltr"><![CDATA[C <h2 style=";text-align:left;direction:ltr"> 56 <h2 style=";text-align:left;direction:ltr"> H<h2 style=";text-align:left;direction:ltr"> 40 <h2 style=";text-align:left;direction:ltr"> IrN3O2<h2 style=";text-align:left;direction:ltr"> 979.27 ≥99.6 G-223 <h2 style=";text-align:left;direction:ltr"><![CDATA[C <h2 style=";text-align:left;direction:ltr"> 62 <h2 style=";text-align:left;direction:ltr"> H<h2 style=";text-align:left;direction:ltr"> 44 <h2 style=";text-align:left;direction:ltr"> D<h2 style=";text-align:left;direction:ltr"> 12 <h2 style=";text-align:left;direction:ltr"> Ge2IrN3O2<h2 style=";text-align:left;direction:ltr"> 1227.32 ≥99.2 G-281 <h2 style=";text-align:left;direction:ltr"><![CDATA[C <h2 style=";text-align:left;direction:ltr"> 70 <h2 style=";text-align:left;direction:ltr"> H<h2 style=";text-align:left;direction:ltr"> 34 <h2 style=";text-align:left;direction:ltr"> D<h2 style=";text-align:left;direction:ltr"> 18 <h2 style=";text-align:left;direction:ltr"> IrN3O2<h2 style=";text-align:left;direction:ltr"> 1177.48 ≥99.2 G-308 <h2 style=";text-align:left;direction:ltr"><![CDATA[C <h2 style=";text-align:left;direction:ltr"> 54 <h2 style=";text-align:left;direction:ltr"> H<h2 style=";text-align:left;direction:ltr"> 36 <h2 style=";text-align:left;direction:ltr"> IrN3O2<h2 style=";text-align:left;direction:ltr"> 951.24 ≥99.5 G-341 <h2 style=";text-align:left;direction:ltr"><![CDATA[C <h2 style=";text-align:left;direction:ltr"> 62 <h2 style=";text-align:left;direction:ltr"> H<h2 style=";text-align:left;direction:ltr"> 52 <h2 style=";text-align:left;direction:ltr"> IrN3O2<h2 style=";text-align:left;direction:ltr"> 1063.37 ≥99.3 G-371 <h2 style=";text-align:left;direction:ltr"><![CDATA[C <h2 style=";text-align:left;direction:ltr"> 58 <h2 style=";text-align:left;direction:ltr"> H<h2 style=";text-align:left;direction:ltr"> 26 <h2 style=";text-align:left;direction:ltr"> D<h2 style=";text-align:left;direction:ltr"> 18 <h2 style=";text-align:left;direction:ltr"> IrN3O2<h2 style=";text-align:left;direction:ltr"> 1025.42 ≥99.4 G-485 <h2 style=";text-align:left;direction:ltr"><![CDATA[C <h2 style=";text-align:left;direction:ltr"> 70 <h2 style=";text-align:left;direction:ltr"> H<h2 style=";text-align:left;direction:ltr"> 34 <h2 style=";text-align:left;direction:ltr"> D<h2 style=";text-align:left;direction:ltr"> 18 <h2 style=";text-align:left;direction:ltr"> IrN3O2<h2 style=";text-align:left;direction:ltr"> 1177.42 ≥99.5 G-591 <h2 style=";text-align:left;direction:ltr"><![CDATA[C <h2 style=";text-align:left;direction:ltr"> 75 <h2 style=";text-align:left;direction:ltr"> H<h2 style=";text-align:left;direction:ltr"> 26 <h2 style=";text-align:left;direction:ltr"> D<h2 style=";text-align:left;direction:ltr"> 28 <h2 style=";text-align:left;direction:ltr"> IrN3O2<h2 style=";text-align:left;direction:ltr"> 1249.56 ≥99.2 G-643 <h2 style=";text-align:left;direction:ltr"><![CDATA[C <h2 style=";text-align:left;direction:ltr"> 58 <h2 style=";text-align:left;direction:ltr"> H<h2 style=";text-align:left;direction:ltr"> 42 <h2 style=";text-align:left;direction:ltr"> DFIrN3O2]]><h2 style=";text-align:left;direction:ltr"> 1026.3 ≥99.1 G-725 <h2 style=";text-align:left;direction:ltr"><![CDATA[C <h2 style=";text-align:left;direction:ltr"> 58 <h2 style=";text-align:left;direction:ltr"> H<h2 style=";text-align:left;direction:ltr"> 34 <h2 style=";text-align:left;direction:ltr"> D<h2 style=";text-align:left;direction:ltr"> 12 <h2 style=";text-align:left;direction:ltr"> GeIrN3O2<h2 style=";text-align:left;direction:ltr"> 1095.32 ≥99.2
[0181] Example 5: Fabrication of an organic electroluminescent device containing organic electroluminescent material G-2
[0182] The I TO glass substrate with a coating thickness of 150nm was cleaned twice in distilled water and ultrasonically washed for 30 minutes, and then repeatedly cleaned twice with distilled water and ultrasonically washed for 10 minutes. After the distilled water cleaning, ultrasonically washed with isopropanol, acetone, methanol and other solvents in sequence, and then dried and transferred to a plasma cleaning machine. The above substrate was washed for 5 minutes and sent to a vapor deposition machine.
[0183] First, 60 nm of 4,4',4"-tri[2-naphthylphenylamino]triphenylamine ("2-TNATA") was vacuum-deposited on ITO (anode) as a hole injection layer; then 60 nm of N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine (NPB) was vacuum-deposited on the hole injection layer as a hole transport layer; and a light-emitting layer was vacuum-deposited on the hole transport layer. The main material of the light-emitting layer, 4,4'-N,N'-biphenyl dicarbazole (CBP) and the doping material compound G-2 were mixed and evaporated at a weight ratio of 95:5. Electroluminescent devices are prepared by vacuum evaporating 30nm of Al to form a light-emitting layer; then vacuum evaporating 10nm thick BAlq to form a hole blocking layer; then vacuum evaporating 40nm thick Alq3 on the hole blocking layer as an electron transport layer; then vacuum evaporating 0.2nm thick LiF on it as an electron injection layer; and then vacuum evaporating 150nm thick Al on the electron injection layer as a cathode. The performance and luminescence characteristics of the obtained electroluminescent device are tested under the condition of a certain brightness. The driving voltage, maximum external quantum efficiency and phosphorescence lifetime are evaluated.
[0184] The material structure used in the device of the present invention is as follows:
[0185]
[0186] Comparative Example:
[0187] An organic electroluminescent device was prepared in the same manner as in Example 5, except that the light-emitting layer doping material G-2 was replaced with compound 1, and the structure of compound 1 is as follows:
[0188]
[0189] The prepared organic electroluminescent device was subjected to the same tests as those in device example 1. The results are shown in Table 2.
[0190] Table 2 Test results of organic electroluminescent devices
[0191] Compound Driving voltage(V) Brightness (cd / cm2) T95(h) EQE(%) Comparative Example 1 4.64 4000 483 14.3 G-2 3.78 4000 662 25.3 G-5 3.86 4000 653 24.2 G-22 3.81 4000 641 26.3 G-374 3.76 4000 658 26.7 G-3 3.82 4000 652 27.4 G-11 3.83 4000 682 26.5 G-18 3.82 4000 638 25.6 G-24 3.75 4000 718 29.1 G-63 3.77 4000 703 32.0 G-209 3.76 4000 690 30.4 G-223 3.86 4000 743 30.3 G-281 3.85 4000 687 28.2 G-308 3.89 4000 670 27.6 G-341 3.77 4000 655 31.2 G-371 3.78 4000 690 29.3 G-485 3.83 4000 741 28.8 G-591 3.77 4000 710 31.8 G-643 3.85 4000 733 31.3 G-725 3.86 4000 727 27.3
[0192] It can be seen from Table 2 that:
[0193] 1) By changing the degree of conjugation of the heterocyclic ligand, the organic electroluminescent material G-18 and compound 1 prepared by the present invention are used in an organic electroluminescent device, and the driving voltage thereof is significantly reduced, the maximum external quantum efficiency is improved, and the life span is significantly improved.
[0194] 2) By introducing the same or different functional groups at different positions of the ligand, the conjugation effect is enhanced, so that after the organic electroluminescent material prepared by the present invention is used in an organic electroluminescent device, the driving voltage is significantly reduced, the maximum external quantum efficiency is improved, and the life span is significantly improved.
[0195] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A doping material, It is characterized in that It has the structure shown in general formula I: wherein m is selected from 0 or 1, and further m is selected from 1; X is selected from O or S; R1, R2, R3, R4, R5, R6, R7, R8, R9, R10, R11, R12, R13, R14, R15, R16, R17, R18, R19, R20, R21 and R22 may be independently selected from hydrogen, deuterium, halogen, cyano, isocyano, substituted or unsubstituted alkyl having 1 to 20 carbon atoms, substituted or unsubstituted cycloalkyl having 3 to 20 carbon atoms, substituted or unsubstituted a heterocyclic group having 3 to 20 carbon atoms, a substituted or unsubstituted aralkyl group having 7 to 30 carbon atoms, a substituted or unsubstituted alkoxy group having 1 to 20 carbon atoms, a substituted or unsubstituted aryloxy group having 6 to 30 carbon atoms, a substituted or unsubstituted aryl group having 6 to 30 carbon atoms, a substituted or unsubstituted heteroaryl group having 3 to 30 carbon atoms, -SiRR'R'', -GeRR'R'', and combinations thereof; Wherein R, R', R'' are selected from substituted or unsubstituted alkyl groups having 1 to 20 carbon atoms, and substituted or unsubstituted cycloalkyl groups having 3 to 20 carbon atoms. Furthermore, the alkyl group and the aryl group may be partially or fully deuterated.
2. The doping material according to claim 1, It is characterized in that Said The ligand is selected from any of the following structures:
3. The doping material according to claim 1, It is characterized in that Said The ligand is selected from any of the following structures:
4. The doping material according to claim 2 and 3, wherein the general formula 1 is selected from one of the following structural formulas I-1, I-2, I-3, I-4 and I-5: wherein R1, R2, R3, R4, R5, R6, R7, R8, R9, R10, R11, R12, R13, R14, R15, R16, R17, R18, R19, R20, R21 and R22 are as defined above.
5. The doping material according to claim 4, It is characterized in that The doping material is selected from any one of the compounds represented by the following structural formulas:
6. An organic electroluminescent device, It is characterized in that The organic electroluminescent device comprises a first electrode, a second electrode, and one or more organic layers disposed between the first electrode and the second electrode; and the organic layers at least comprise one or more of a hole injection layer, a hole transport layer, a layer having both hole injection and hole transport skills, an electron blocking layer, a light-emitting layer, a hole blocking layer, an electron transport layer, an electron injection layer, and a layer having both electron transport and electron injection skills; and the light-emitting layer comprises the doping material as described in claim 1.
7. The organic electroluminescent device according to claim 6, It is characterized in that The light-emitting layer of the organic electroluminescent device comprises a main material and a doping material, the doping material is the organic metal iridium complex, and the mixing ratio of the main material to the doping material is 90:10 to 99.5:0.
5.
8. An organic electroluminescent device, It is characterized in that The organic electroluminescent device comprises the organic electroluminescent device according to claim 6.
